PYGMALION ÎN ŞCOALĂ. CE FACEM CU EL? - USM ADMIN (Moldova State University, 2010)
Speaking about the objective evaluation of the efficiency of education, it is very important to point out the need to ensure a docimologic climate of maximal correctness and impartiality. It is well known that the factors that generate a low objectivity while appreciating school results can be first of all related to the teacher's personality and that of the student. Out of all these factors the Pygmalion effect stands out. As the Pygmalion effect has a bad influence on the didactic evaluation, it is extremely important to learn the practical modalities in "limiting its possibilities". A meticulous analysis of the sources- especially of studies centered round the identification of "forms, methods and means which ensure a correct and objective appreciation of knowledge or abilities"- show that this problem is not knew (several generations of analysts of the educational field have been struggling with it) and that, up to this moment, a solution can be found every time one resorts to the (a) organization of some external examinations (where teaching staff from other institutional environments are invited to participate), (b) extension of works with a secret character (meaning works that ensure the anonymity of those to be appreciated), (c) involving several teachers in the process of evaluating one and the same student and (d) comparing the results of the evaluation with those accomplished in time by the school inspectors or any other person with control function (principal, vice-principal, class teacher, etc.).